Russia's Military Action in Syria Driven by Military Reforms. Issue 2 (2nd April 2020) - de Haas, Mordechai; Gaberščik, E.; Jenkins, T.; Kumar, A.
ABSTRACT: The August 2008 war of Russia against Georgia, showing severe shortcomings in Russia's military capabilities, made Moscow realize that modernization of its armed forces was inevitable to effectively use military power as a policy instrument. Hence, a military reform plan (2008–2020) was initiated. This article demonstrates how since September 2015, Moscow's army has utilized the Syrian conflict as a testing ground for its military reforms. What conclusions can be drawn from the use of Russian military power in Syria, in relation to its military modernization?